Damage-based design with no repairs for multiple events and its sensitivity to seismicity model. - Das, S.
Conventional design methodology for the earthquake-resistant structures is based on the concept of ensuring ?no collapse? during the most severe earthquake event. This methodology does not envisage the possibility of continuous damage accumulation during several not-so-severe earthquake events, as may be the case in the areas of moderate to high seismicity, particularly when it is economically infeasible to carry out repairs after damaging events. As a result, the structure may collapse or may necessitate large scale repairs much before the design life of the structure is over. This study considers the use of design force ratio (DFR) spectrum for taking an informed decision on the extent to which yield strength levels should be raised to avoid such a scenario. DFR spectrum gives the ratios by which the yield strength levels of single-degree-of-freedom oscillators of different initial periods should be increased in order to limit the total damage caused by all earthquake events during the lifetime to a specified level. The DFR spectra are compared for three different seismicity models in case of elasto-plastic oscillators: one corresponding to the exponential distribution for return periods of large events and the other two corresponding to the lognormal and Weibull distributions. It is shown through numerical study for a hypothetical seismic region that the use of simple exponential model may be acceptable only for small values of the seismic gap length. For moderately large to large seismic gap lengths, it may be conservative to use the lognormal model, while the Weibull model may be assumed for very large seismic gap lengths.
Keywords: Cumulative damage; Design force ratio spectrum; Performance-based design; Seismicity model; Order statistics; Hazard function